2010
DOI: 10.2334/josnusd.52.1
|View full text |Cite
|
Sign up to set email alerts
|

Emdogain® in carcinogenesis: a systematic review of in vitro studies

Abstract: Emdogain is a commercial product of unknown composition and is clinically used to induce periodontal regeneration. This study aims to review current knowledge of the in vitro effects of Emdogain on oral tissues and, in particular, factors related to carcinoma. A systematic approach was used to review studies from the Embase and Pubmed databases; a total of 76 studies were included. These comprised in vitro studies of the cytokines in, or regulated by, Emdogain and assays designed to study the effects of EMD on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 108 publications
(76 reference statements)
1
6
0
Order By: Relevance
“…Previous studies conducted on cervical cancer cells indicated that EMD has an inhibitory effect on epithelial cells (13,27). Lyngstadaas et al (15) showed that HeLa cells growing in the presence of EMD exhibited a highly increased intracellular level of cyclic adenosine monophosphate compared with controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies conducted on cervical cancer cells indicated that EMD has an inhibitory effect on epithelial cells (13,27). Lyngstadaas et al (15) showed that HeLa cells growing in the presence of EMD exhibited a highly increased intracellular level of cyclic adenosine monophosphate compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…Results concerning the influence of EMD on oral epithelial cells are particularly ambiguous; EMD was determined to have an anti-proliferative effect on epithelial cells (12,13), but numerous clinicians have observed accelerated epithelial soft-tissue healing upon intrasurgical application of EMD (2629). It has been suggested that EMD may induce alterations in malignant mucosal tissue, which implies that patients with pre-malignant or malignant mucosal lesions should not be treated with EMD (27). …”
Section: Discussionmentioning
confidence: 99%
“…The results of research on the effects of EMD on oral epithelial cells are ambigu- ous. EMD has been shown to decrease the proliferation of epithelial cells [27,28], but in many clinical trials, the acceleration of epithelial healing after intraoperative EMD use was observed [29][30][31][32]. It is suggested that EMD may induce malignant lesions in the mucosa, which means that patients with pre-cancerous or malignant lesions on the mucosa should not be treated with EMD [30].…”
Section: Amelogenins Influence On Epithelial Cellsmentioning
confidence: 99%
“…Kawase et al (46) postulated that EMD reduced DNA synthesis, suggesting that a reduction in epithelial cell growth could be mediated by TGF-β-like activity. EMD and TGF-β are also able to stimulate the production of matrix metalloproteinases (MMPs), which are crucial in tumorigenesis and in benign keratinocytes (27).…”
Section: Tgf-β In the Periodontiummentioning
confidence: 99%
“…While EMD presents a number of growth factor-like effects, it is the TGF-β activity that is predominately known (23)(24)(25)(26). EMD has also been reported to contain other cytokines, such as a BMP-like growth factor and bone sialoprotein (BSP)-like molecules (27,28).…”
Section: Introductionmentioning
confidence: 99%